Extreme prematurity and sepsis strongly influence frequencies and functional characteristics of circulating γδ T and natural killer cells - Khaleda Rahman Qazi; Georg B Jensen; Marieke van derHeiden; Sophia Björkander; Giovanna Marchini; Maria C Jenmalm; Thomas Abrahamsson; Eva Sverremark‐Ekström (Clinical & Translational Immunology, 2021)
Abstract Objectives Extremely low gestational age neonates with extremely low birthweight (ELGAN/ELBW) are highly susceptible to infection. This is linked to their relatively immature immune system which is not yet fully compatible with an extra‐uterine environment. Here, we performed a longitudinal characterisation of unconventional T and natural killer (NK) cells in ELGAN/ELBW during their first months of life. Methods Peripheral blood mononuclear cells were collected from 97 ELGAN/ELBW at 14 and 28 days of life and at a time point corresponding to postmenstrual week 36 + 0. γδ T‐cell, NKT‐cell, mucosa‐associated invariant T‐cell and NK cell frequencies and characteristics were analysed by flow cytometry. As control, cells from 14‐day‐old full‐term (FT) infants were included. Results Extreme prematurity had significant bearing on γδ T‐cell and NK cell frequencies and characteristics. ELGAN/ELBW had significantly higher proportions of γδ T cells that were skewed towards effector and effector memory phenotypes, characteristics that were maintained throughout the study period. Expression of the gut homing receptor CCR9 was also more common in γδ T cells from ELGAN/ELBW. Conversely, NK cell frequencies were markedly lower and skewed towards a cytotoxic phenotype in the ELGAN/ELBW group at 14 days of age. Culture‐proven sepsis with an onset during the first 14 days after birth further manifested these differences in the γδ T‐ and NK cell populations at 14 days of age. Conclusion Prematurity strongly influences the levels of γδ T and NK cells, in particular in cases where sepsis debuts during the first 2 weeks of life.